LGBT+ young people in contemporary Italy between cultural consumption and relational technologies - Corbisiero, Fabio; Urciuoli, Carmine (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2019)
In last decades, the issues of equality and social justice faced by LGBT+ people for the conquest of social and civil rights, especially by the young, have allowed the formulation of a new form of citizenship that has placed itself at the top of the political agenda of all western countries. In Italy, the rights of homosexual people have only been partially institutionalized in legislation, while sociological research has begun to consider how some cultural consumption among homosexual young people can facilitate more inclusive relationship circles for LGBT young people. Given the focus of the LGBT Observatory of the Department of Social Sciences of the University of Naples Federico II, this study examines the ways in which cultural devices and mass media represent and build sexual identity and citizenship.